2022
DOI: 10.3389/fevo.2022.907666
|View full text |Cite
|
Sign up to set email alerts
|

Starch granules from human teeth: New clues on the Epi-Jomon diet

Abstract: This study examined starch granules from the dental calculus of specimens from the Epi-Jomon (Zoku-Jomon in Japanese, ca. 350 BCE–350 CE) period in Japan for taxonomic identification of plant food items and the reconstruction of human socioeconomic practices. Dental calculus was extracted from 21 individuals across six Epi-Jomon sites in Hokkaido. Moreover, 12 starch granules and starch clusters were recovered from nine individuals. The morphologies of the extracted starch granules were then classified into fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In the case of Hokkaido this is certainly not true, as a distinct shift is seen in all three of these areas. Technologies introduced at the time include metal tools and specialist fishing items; economic changes are seen in changes to subsistence practices and trade items (Aono, 2021in Shibutani et al, 2022; and cultural change is indicated by shifts in material culture and architecture but also by shifts in regional burial practices, as will be seen. Rather than hunter-gatherers continuing to live a Jomon way of life during this period, they changed and adapted, and played an important role in contemporary regional trade networks.…”
Section: Diversity Among Hunter-gatherers: the Example Of Hokkaido's ...mentioning
confidence: 99%
“…In the case of Hokkaido this is certainly not true, as a distinct shift is seen in all three of these areas. Technologies introduced at the time include metal tools and specialist fishing items; economic changes are seen in changes to subsistence practices and trade items (Aono, 2021in Shibutani et al, 2022; and cultural change is indicated by shifts in material culture and architecture but also by shifts in regional burial practices, as will be seen. Rather than hunter-gatherers continuing to live a Jomon way of life during this period, they changed and adapted, and played an important role in contemporary regional trade networks.…”
Section: Diversity Among Hunter-gatherers: the Example Of Hokkaido's ...mentioning
confidence: 99%